A diagnostic model for adoption of human resources analytics in local subsidiaries : study focused on multi-national enterprises (MNEs) in Sub-Saharan Africa - Wocke, Albert (University of Pretoria, 2017)
Mini Dissertation (MBA)--University of Pretoria, 2017.